2023
DOI: 10.29122/mipi.v16i2.5255
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Padeye Placement on Ship Block Lifting

Abstract: Nowadays, steel ship construction in Indonesia is dominated by the hull block construction method. This method can reduce man-hours as the ship is manufactured by a division of the hull into several sections/blocks; here, it can be worked in parallel. Once work is finished on these blocks and then proceeding to the main hull for assembling, the lifting operation is performed on the blocks during this erecting process. Lifting of ship blocks must be planned safely to avoid damage. One of the items that must be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…The results of eye-bearing size optimization revealed a 50% saving in steel costs. Arifuddin et al [ 10], simulated the placement of a lifting pad eye to obtain the most optimal position using the stiffness method. The results of the study revealed that the location of the pad eye greatly influences the bending stress and deformation of the ship block.…”
Section: Pad Eyementioning
confidence: 99%
“…The results of eye-bearing size optimization revealed a 50% saving in steel costs. Arifuddin et al [ 10], simulated the placement of a lifting pad eye to obtain the most optimal position using the stiffness method. The results of the study revealed that the location of the pad eye greatly influences the bending stress and deformation of the ship block.…”
Section: Pad Eyementioning
confidence: 99%